High-strength corrosion-resistant 6XXX series aluminum alloy and preparation method thereof
By adding chromium to the 6xxx series aluminum alloy with high copper content, adjusting the Cr:Cu ratio, and forming a dispersion to control the microstructure of the grain boundary, the problem of aluminum alloy being prone to corrosion at the grain boundary is solved, and higher corrosion resistance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202380055908.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-07-05
- Publication Date
- 2025-03-11
AI Technical Summary
High copper content 6xxx series aluminum alloys are prone to form Cu-rich films and Q-phase precipitated particles at grain boundaries, resulting in intergranular corrosion (IGC) problems.
By adding an appropriate amount of chromium (Cr) to the aluminum alloy, the ratio of Cr:Cu is adjusted to form more dispersions to control grain size and grain boundary microstructure, thereby reducing Cu segregation and Q phase formation.
The intergranular corrosion depth of aluminum alloy is significantly reduced, its corrosion resistance is improved, and high strength and formability are maintained.
Smart Images

Figure CN119604636A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of and priority to U.S. Provisional Application No. 63 / 369,307, filed on July 25, 2022, which is incorporated herein by reference in its entirety for all intents and purposes. Technical Field
[0003] The present disclosure relates to metallurgy, aluminum alloys, aluminum processing fields and related fields. Specifically, the present disclosure generally provides a novel 6xxx series aluminum alloy with high corrosion resistance. The present disclosure also provides various end uses of such products, such as end uses in automobiles, transportation, electronics, industry, aerospace and other applications. Background Art
[0004] High-strength aluminum alloys are used in many different applications, particularly in applications requiring strength and durability. For example, 6xxx series aluminum alloys are widely used in automotive applications due to their excellent property combination (including strength to weight ratio, formability, weldability and general corrosion resistance). 6xxx series aluminum alloys are usually used in automotive structures and closed plate applications instead of steel. Since the density of aluminum alloys is usually about 2.8 times lower than that of steel, this type of material is used to reduce the weight of the vehicle and allow significantly improved fuel economy. Even so, currently available aluminum alloys are still faced with certain challenges in automotive applications.
[0005] Specifically, for 6xxx series aluminum alloys with high copper (Cu) content (e.g., greater than 0.50 wt. % Cu), Cu may segregate at grain boundaries and form Cu-rich films and precipitate phase particles. For example, Cu in 6xxx series aluminum alloys may form Q-phase precipitate particles (e.g., Al5Cu2Mg8Si6). Compared with the precipitation-free zone near the grain boundary, the Q-phase precipitate particles and the Cu-rich film at the grain boundary both act as cathodes, thereby causing intergranular corrosion (IGC). Therefore, 6xxx series aluminum alloys containing Cu may be more susceptible to IGC. Summary of the invention
[0006] The embodiments covered by the present disclosure are defined by the claims rather than by this Summary. This Summary is a high-level overview of various aspects of the invention and introduces some concepts that are further described in the Detailed Description section below. This Summary is not intended to identify the key features or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to appropriate portions of the entire specification, any or all of the drawings, and each claim.
[0007] The aluminum alloy described herein includes 0.50 to 2.50 wt. % Si, 0.10 to 0.50 wt. % Fe, 0.01 to 1.20 wt. % Cu, 0.01 to 0.50 wt. % Mn, 0.30 to 1.50 wt. % Mg, 0.05 to 0.50 wt. % Cr, 0.01 to 0.50 wt. % Zn, up to 0.20 wt. % Zr, up to 0.15 wt. % impurities, and Al. In some embodiments, the aluminum alloy includes 0.60 to 2.25 wt % Si, 0.15 to 0.50 wt % Fe, 0.01 to 1.00 wt % Cu, 0.04 to 0.45 wt % Mn, 0.35 to 1.30 wt % Mg, 0.10 to 0.50 wt % Cr, 0.01 to 0.40 wt % Zn, up to 0.20 wt % Zr, up to 0.15 wt % impurities, and Al. In some embodiments, the aluminum alloy includes 0.70 to 2.0 wt % Si, 0.20 to 0.50 wt % Fe, 0.05 to 1.00 wt % Cu, 0.04 to 0.40 wt % Mn, 0.40 to 1.20 wt % Mg, 0.10 to 0.45 wt % Cr, 0.01 to 0.30 wt % Zn, up to 0.15 wt % Zr, up to 0.15 wt % impurities, and Al. In some embodiments, the aluminum alloy includes 0.80 to 1.9 wt % Si, 0.23 to 0.50 wt % Fe, 0.20 to 1.00 wt % Cu, 0.15 to 0.40 wt % Mn, 0.45 to 1.00 wt % Mg, 0.15 to 0.45 wt % Cr, 0.01 to 0.20 wt % Zn, 0.01 to 0.10 wt % Zr, up to 0.15 wt % impurities, and Al. In some embodiments, the aluminum alloy comprises 1.00 to 1.70 wt % Si, 0.30 to 0.45 wt % Fe, 0.30 to 0.80 wt % Cu, 0.20 to 0.40 wt % Mn, 0.50 to 0.90 wt % Mg, 0.20 to 0.40 wt % Cr, 0.01 to 0.15 wt % Zn, 0.05 to 0.10 wt % Zr, up to 0.15 wt % impurities, and Al. In some embodiments, the ratio of Cr:Cu is at least 0.25:1. In some embodiments, the aluminum alloy comprises 0.20 to 0.50 wt % Cu, 0.05 to 0.30 wt % Cr, and the ratio of Cr:Cu is at least 0.3:1. In some embodiments, the aluminum alloy comprises greater than 0.50 wt % Cu, 0.20 to 0.50 wt % Cr, and the ratio of Cr:Cu is at least 0.5:1. In some embodiments, the aluminum alloy has a yield strength of at least 300 MPa when in a T6 temper. In some embodiments, the aluminum alloy has an ultimate tensile strength of at least 350 MPa when in a T6 temper.In some embodiments, the aluminum alloy includes an inner bend angle of less than 140° when in T6 tempering, as measured according to VDA238-100 (2022). In some embodiments, the aluminum alloy is pre-strained. In some embodiments, the aluminum alloy is pre-strained, and when subjected to the intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours, the maximum corrosion depth of the aluminum alloy is less than 300 μm. In some embodiments, the aluminum alloy is in T4 tempering. In some embodiments, the aluminum alloy is aged without pre-straining. In some embodiments, the aluminum alloy is artificially aged. In some embodiments, when subjected to the intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours, the maximum corrosion depth of the aluminum alloy is less than 400 μm.
[0008] Described herein is a method for producing an aluminum alloy, comprising: casting an aluminum alloy to form a cast product, wherein the aluminum alloy comprises 0.50 to 2.50 wt% Si, 0.10 to 0.50 wt% Fe, 0.01 to 1.20 wt% Cu, 0.01 to 0.50 wt% Mn, 0.30 to 1.50 wt% Mg, 0.05 to 0.50 wt% Cr, 0.01 to 0.50 wt% Zn, up to 0.20 wt% Zr, up to 0.15 wt% impurities, and Al; homogenizing the cast product; hot rolling the cast product to produce a hot rolled product; cold rolling the rolled product to produce a rolled product of final specification; and solution heat treating the rolled product of final specification. In some embodiments, the method further comprises aging the rolled product of final specification to T temper. In some embodiments, T temper is T4 temper, T6 temper or T8x temper. In some embodiments, the method further comprises pre-straining the final specification rolled product. In some embodiments, the method further comprises subjecting the final specification rolled product to natural aging to T4 tempering, and subjecting the final specification rolled product to artificial aging at a temperature of 150°C to 200°C for 10 min to 1 hour, wherein when subjected to the intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours, the maximum corrosion depth of the final specification rolled product is less than 300 μm.
[0009] Other aspects, objects and advantages will become apparent upon consideration of the following detailed description and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Provided is a graph of average and maximum intergranular corrosion (IGC) depths of example aluminum alloys measured according to ISO 11846B (2022) after immersion for 24 hours according to some embodiments described herein.
[0011] Figure 2 Provided are images of contour plots of IGC depth versus the amount of Cr and Cu in an example aluminum alloy when the example aluminum alloy is in a T4 temper and artificially aged at 180° C. for 0.5 hours according to some embodiments described herein.
[0012] Figure 3 Provided are images of contour plots of IGC depth versus Cr and Cu content in an aluminum alloy when the aluminum alloy is in T4 temper, 10% pre-strained, and artificially aged at 180° C. for 1 hour, according to some embodiments described herein.
[0013] FIG. 4A to FIG. 4D Example 1 ( Figure 4A and Figure 4C ) and Comparative Example 3 ( Figure 4B and Figure 4D ) is a scanning transmission electron microscopy (STEM) image of the grain boundaries of .
[0014] FIG. 5A to FIG. 5C STEM images of grain boundaries of Example 1 and Comparative Example 3 according to some embodiments described herein are provided.
[0015] 6A to 6H An energy dispersive spectroscopy (EDS) graph of Example 1 is provided according to some embodiments described herein.
[0016] 7A to 7H An EDS graph of Comparative Example 3 according to some embodiments described herein is provided.
[0017] Fig. 8A and Figure 8B Electron backscatter diffraction (EBSD) grain morphology images of Example 1 and Comparative Example 3 according to some embodiments described herein are provided. DETAILED DESCRIPTION
[0018] This paper describes a novel 6xxx series aluminum alloy, which shows high corrosion resistance while maintaining high strength to weight ratio, formability and weldability. In addition, aluminum alloys as described herein include a relatively high amount of trace alloying elements (e.g., chromium (Cr) and zirconium (Zr)) to improve the corrosion resistance of products formed by aluminum alloys without causing a significant loss of strength. Without being bound by any particular theory, it is believed that including a relatively high amount of trace alloying elements results in the formation of a large amount of dispersoids during homogenization, which can serve as nucleation sites for precipitation (such as precipitation phase particles (e.g., Q phase precipitation) containing Cu). Since these precipitations are formed at the position of dispersoids, they are not formed in large quantities at the grain boundaries of aluminum alloys. Therefore, aluminum alloys as described herein are significantly less prone to intergranular corrosion than conventional 6xxx series aluminum alloys.
[0019] Because aluminum alloy has the passivation film (for example, several nanometers thick) formed naturally by air oxidation, it shows good uniform corrosion resistance. However, when exposed to corrosive environment (for example, chloride-containing electrolyte), the passivation film can be easily destroyed in local parts, thereby causing local corrosion. Specifically, 6xxx series aluminum alloys containing Cu are prone to IGC under corrosive environment. For some 6xxx series aluminum alloys, overaging improves IGC resistance. For example, by extending the aging time and pre-strain treatment separately, the maximum depth of IGC of some 6xxx series aluminum alloys can be reduced. However, this process may increase production time, and may reduce the overall formability of 6xxx series aluminum alloys.
[0020] Novel 6xxx series aluminum alloys as described herein include Cr to improve IGC resistance. Specifically, when including Cr content as described herein, 6xxx series aluminum alloys including low amount of Cu (0.01 to 0.20 weight %), medium amount of Cu (e.g., 0.20 to 0.50 weight %) and high amount of Cu (greater than 0.50 weight %) each show a significant improvement in IGC resistance. For example, when providing a specific Cr and Cu ratio as further described below, the IGC maximum depth of the 6xxx series aluminum alloy containing Cu in a corrosive environment is significantly reduced. In fact, even compared with the 6xxx series aluminum alloys with low amount of Cu, the 6xxx series aluminum alloys with the Cr of the amount of 0.05 weight % to 0.50 weight % also improve the IGC resistance of the aluminum alloy with high amount of Cu. In addition, research finds that Cr addition and the combination of extended aging and prestrain synergistically improve the IGC resistance of the 6xxx series aluminum alloys. The 6xxx series aluminum alloys described herein exhibit reduced segregation at grain boundaries due to prestraining and extended aging time, which reduces the microgalvanic effect between the copper-rich film and the precipitation-free zone at the grain boundaries, thereby reducing the susceptibility of the aluminum alloy to IGC.
[0021] Definition and Description
[0022] As used herein, the terms "invention," "the invention," "this invention," and "the present invention" are intended to refer broadly to the subject matter of this patent application and the claims that follow in their entirety. Statements containing these terms should not be construed as limiting the subject matter described herein or limiting the meaning or scope of the patent claims that follow.
[0023] In this description, reference is made to alloys identified by aluminum industry designations, such as "Series" or "6xxx." To understand the numerical designation system most commonly used in naming and identifying aluminum and its alloys, see "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Compositions Limits for Aluminum Alloys in the Form of Castings and Ingot," both published by the Aluminum Association.
[0024] As used herein, the meaning of "a", "an" or "the" includes both singular and plural referents unless the context clearly indicates otherwise.
[0025] As used herein, a plate generally has a thickness greater than about 15 mm. For example, a plate may refer to an aluminum product having a thickness greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, or greater than about 100 mm.
[0026] As used herein, the thickness of the satt board (also referred to as a sheet board) is generally about 4 mm to about 15 mm. For example, the satt board can have a thickness of about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm, or about 15 mm.
[0027] As used herein, sheet generally refers to an aluminum product having a thickness of less than about 4 mm (eg, less than 3 mm, less than 2 mm, less than 1 mm, less than 0.5 mm, less than 0.3 mm, or less than 0.1 mm). For example, the sheet can have a thickness of about 0.1 mm, about 0.2 mm, about 0.3 mm, about 0.4 mm, about 0.5, about 0.6 mm, about 0.7 mm, about 0.8 mm, about 0.9 mm, about 1 mm, about 1.1 mm, about 1.2 mm, about 1.3 mm, about 1.4 mm, about 1.5 mm, about 1.6 mm, about 1.7 mm, about 1.8 mm, about 1.9 mm, about 2 mm, about 2.1 mm, about 2.2 mm, about 2.3 mm, about 2.4 mm, about 2.5 mm, about 2.6 mm, about 2.7 mm, about 2.8 mm, about 2.9 mm, about 3 mm, about 3.1 mm, about 3.2 mm, about 3.3 mm, about 3.4 mm, about 3.5 mm, about 3.6 mm, about 3.7 mm, about 3.8 mm, about 3.9 mm, or about 4 mm.
[0028] As used herein, formability refers to the ability of a material to be deformed into a desired shape without breaking, tearing, necking, bulging, or forming errors such as wrinkling, springback, or wear. In engineering, formability can be classified according to the deformation mode. Examples of deformation modes include drawing, stretching, bending, and stretch flanging.
[0029] As used herein, “precipitation phase particles” means equilibrium phase particles of the metastable phase of the 6xxx series aluminum alloy, such as Mg2Si (β phase) particles and Al5Cu2Mg8Si6 (Q phase) particles, and the like.
[0030] Reference may be made to alloy tempers or conditions in this application. For the most commonly used alloy temper descriptions, see "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". The F condition or temper refers to a manufactured aluminum alloy. The O condition or temper refers to an aluminum alloy after annealing. The Hxx condition or temper, also referred to herein as the H temper, refers to a non-heat-treatable aluminum alloy that has been subjected to or not subjected to heat treatment (e.g., annealing) after cold rolling. Suitable H tempers include HX1, HX2, HX3, HX4, HX5, HX6, HX7, HX8 or HX9 tempers. The T1 condition or temper refers to an aluminum alloy that has been cooled from hot working and naturally aged (e.g., at room temperature). The T2 condition or temper refers to an aluminum alloy that has been cooled from hot working, cold worked and naturally aged. The T3 condition or temper refers to an aluminum alloy that has been solution heat treated, cold worked and naturally aged. The T4 condition or temper refers to an aluminum alloy that has been solution heat treated and naturally aged. The T5 temper or temper refers to aluminum alloys that have been cooled from hot working and artificially aged (at elevated temperatures). The T6 temper or temper refers to aluminum alloys that have been solution heat treated and artificially aged. The T7 temper or temper refers to aluminum alloys that have been solution heat treated and artificially overaged. The T8x temper or temper refers to aluminum alloys that have been solution heat treated, cold worked, and artificially aged. The T9 temper or temper refers to aluminum alloys that have been solution heat treated, artificially aged, and cold worked. The W temper or temper refers to aluminum alloys that have been solution heat treated.
[0031] As used herein, "room temperature" may include temperatures from about 15°C to about 30°C, for example, about 15°C, about 16°C, about 17°C, about 18°C, about 19°C, about 20°C, about 21°C, about 22°C, about 23°C, about 24°C, about 25°C, about 26°C, about 27°C, about 28°C, about 29°C or about 30°C.
[0032] All ranges disclosed herein should be understood to cover both endpoints and any and all subranges included therein. For example, the range of "1 to 10" should be considered to include any and all subranges between a minimum value of 1 and a maximum value of 10 (and including the end values); that is, all subranges start with a minimum value of 1 or a greater number, such as 1 to 6.1, and end with a maximum value of 10 or a lesser number, such as 5.5 to 10.
[0033] The following aluminum alloys are described with elemental composition in weight percent (wt%) based on the total weight of the alloy. In certain examples of each alloy, the remainder is aluminum, with a maximum wt% of the sum of impurities of 0.15%.
[0034] Alloy composition
[0035] Aluminum alloy properties are determined in part by the composition of the aluminum alloy. In certain aspects, the alloy composition can influence or even determine whether the alloy will have properties sufficient for a desired application.
[0036] New 6xxx series aluminum alloys are described herein. The aluminum alloys exhibit high yield strength and bendability, as well as unexpectedly high corrosion resistance at grain boundaries. The properties of the aluminum alloys are achieved due to the composition and / or manufacturing method of the alloy.
[0037] In some examples, aluminum alloys as described herein may have the following elemental compositions as provided in Table 1.
[0038] Table 1
[0039]
[0040]
[0041] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 2.
[0042] Table 2
[0043]
[0044] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 3.
[0045] Table 3
[0046]
[0047]
[0048] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 4.
[0049] Table 4
[0050]
[0051] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 5.
[0052] Table 5
[0053]
[0054] Silicon (Si)
[0055] In some examples, the aluminum alloys described herein include Si in an amount of 0.50% to 2.50% (e.g., 0.60% to 2.25%, 0.70% to 2.00%, 0.80% to 1.90%, or 1.00 wt. % to 1.70 wt. %) based on the total weight of the alloy. For example, the alloy may include 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 0.100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 118%, 119%, 120%, 121%, 122%, 123%, 124%, 125%, 126%, 127%, 128%, 129%, 130%, 131%, 132%, 133%, 134%, 135%, 136%, 137%, 138%, 139%, 1 86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27%, 1.28%, 1.29%, 1.30%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.39%, 1.40%, 1.41%, 1.42%, 1.43%, 1.44%, 1.45%, 1.46%, 1.47%, 1.48%, 1.49%, 1.50%, 1.51%, 1.52%, 1.53%, 1.54%, 1.55%, 1.56%, 1.57%, 1.58%, 1.59%, 1.60%, 1.61 %, 1.62%, 1.63%, 1.64%, 1.65%, 1.66%, 1.67%, 1.68%, 1.69%, 1.70%, 1.71%, 1.72%, 1.73%, 1.74%, 1.75%, 1.76%, 1.77%, 1.78%, 1.79%, 1.80%, 1.81%, 1.82%, 1.83%, 1.84%, 1.85%, 1.86%, 1.87%, 1.88%, 1.89%, 1.90%, 1.91%, 1.92%, 1.93%, 1.94%, 1.95%, 1.96%, 1.97%, 1.98%, 1.99%, 2.00%, 2.01%, 2.02%, 2.03%, 2.04%, 2.05%, 2.06%, 2.07%, 2.08%, 2.09%, 2.10%, 2.11%, 2.12%, 2.13%, 2.14%, 2.15%, 2.16%, 2.17%, 2.18%, 2.19%, 2.20%, 2.21%, 2.22%, 2.23%, 2.24%, 2.25%, 2.26%, 2.27%, 2.28%, 2.29%, 2.30%, 2.31%, 2.32%, 2.33%, 2.34%, 2.35%, 2.36%, 2.37%, 2.38%, 2.39%, 2.40%, 2.41%, 2.42%, 2.43%, 2.44%, 2.45%, 2.46%, 2.47%, 2.48%, 2.49% or 2.50% Si. All are by weight. .
[0078] Iron (Fe)
[0079] In some examples, the aluminum alloys described herein further include Fe in an amount of 0.10% to 0.50% (e.g., 0.15% to 0.50%, 0.20% to 0.50%, 0.23% to 0.50%, or 0.30% to 0.45%) based on the total weight of the alloy. For example, the alloy may include 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.7 %, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49% or 0.50% Fe. All are expressed in weight %.
[0080] Copper (Cu)
[0081] In some examples, the aluminum alloys described herein include Cu in an amount of 0.01 to 1.20% (eg, 0.01 to 1.00%, 0.05 to 1.00%, 0.20 to 1.00%, or 0.30 to 0.80%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%. , 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0. .60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.9 0%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19% or 1.20% Cu. All are expressed in weight %.
[0082] Manganese (Mn)
[0083] In some examples, the aluminum alloys described herein may include Mn in an amount of 0.01% to 0.50% (e.g., 0.04% to 0.45%, 0.04% to 0.40%, 0.15% to 0.40%, or 0.20% to 0.40%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0. %. 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49% or 0.50% Mn. All are expressed in weight %.
[0084] Magnesium (Mg)
[0085] In some examples, the aluminum alloys described herein may include Mg in an amount of 0.30% to 1.50% (eg, 0.35% to 1.30%, 0.40% to 1.20%, 0.45% to 1.00%, 0.50 to 0.90%) based on the total weight of the alloy. For example, the alloy may include 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 0.91%, 0.92%, 0.9 .59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89 %, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1 %. 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27%, 1.28%, 1.29%, 1.30%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.39%, 1.40%, 1.41%, 1.42%, 1.43%, 1.44%, 1.45%, 1.46%, 1.47%, 1.48%, 1.49% or 1.50% Mg. All are expressed in weight %.
[0086] Zinc (Zn)
[0087] In some examples, the aluminum alloys described herein include Zn in an amount of 0.01% to 0.50% (e.g., 0.01% to 0.40%, 0.01% to 0.30%, 0.01% to 0.20%, or 0.01% to 0.15%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.6 %. In some cases, Zn is absent from the alloy (i.e., 0%). All are expressed in wt %.
[0088] Zirconium (Zr)
[0089] In some examples, the aluminum alloys described herein include Zr in an amount up to 0.20% (e.g., up to 0.15%, up to 0.10%, 0.01% to 0.20%, 0.01% to 0.15%, 0.01% to 0.10%, or 0.05% to 0.10%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.20% Zr. In some cases, Zr is absent from the alloy (i.e., 0%). All are expressed in weight %.
[0090] Chromium (Cr)
[0091] In some examples, the aluminum alloys described herein include Cr in an amount of 0.05% to 0.20% (e.g., 0.10% to 0.50%, 0.10% to 0.45%, 0.15% to 0.45%, or 0.20% to 0.40%) based on the total weight of the alloy. For example, the alloy may include 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.7 %. 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49% or 0.50% Cr. All are expressed in weight %.
[0092] In some embodiments, the aluminum alloy includes a Cr:Cu ratio that beneficially reduces IGC. In some embodiments, the Cr:Cu ratio is greater than 0.1:1 (e.g., greater than 0.2:1, greater than 0.25:1, greater than 0.5:1, greater than 0.75:1, greater than 0.8:1, greater than 0.9:1, greater than 1:1, greater than 2:1, greater than 4:1, greater than 5:1, greater than 6:1, greater than 8:1, or greater than 9:1). In some embodiments, the Cr:Cu ratio ranges from 0.1:1 to 10:1 (e.g., 0.25:1 to 8:1, 0.5:1 to 6:1, 0.8:1 to 5:1, 1:1 to 5:1, 1:1 to 4:1, or 1:1 to 3:1).
[0093] In some embodiments, the amount of Cr added to the 6xxx series aluminum alloy is related to the Cu content in the aluminum alloy. For example, 0.05 wt % to 0.20 wt % Cr may be added to a 6xxx series aluminum alloy comprising 0.01 wt % to 0.20 wt % Cu. In some embodiments, 0.05 wt % to 0.20 wt % Cr may be added to a 6xxx series aluminum alloy comprising 0.20 wt % to 0.50 wt % Cu. In some embodiments, 0.10 wt % to 0.50 wt % Cr may be added to a 6xxx series aluminum alloy comprising greater than 0.50 wt % Cu.
[0094] In some embodiments, a 6xxx series aluminum alloy may include 0.01 to 0.20 wt % Cu, 0.05 to 0.20 wt % Cr, and a Cr:Cu ratio of at least 0.25: 1. In some embodiments, a 6xxx series aluminum alloy may include 0.20 to 0.50 wt % Cu, 0.05 to 0.30 wt % Cr, and a Cr:Cu ratio of at least 0.5: 1. In some embodiments, a 6xxx series aluminum alloy may include greater than 0.50 wt % Cu, 0.25 to 0.50 wt % Cr, and a Cr:Cu ratio of at least 1:1.
[0095] Trace Elements
[0096] Optionally, the aluminum alloys described herein may further include other trace elements (sometimes referred to as impurities) in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. These impurities may include, but are not limited to, Ti, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, Pb, or a combination thereof. Thus, Ti, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, or Pb may be present in the alloy in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. The sum of all impurities does not exceed 0.15% (e.g., 0.1%). All are expressed in weight %. The remaining percentage of each alloy may be aluminum.
[0097] nature
[0098] In some examples, an aluminum alloy product (e.g., an aluminum alloy sheet) produced from an aluminum alloy described herein may have a yield strength of 250 MPa or greater when in a T6 temper. For example, an aluminum alloy product produced from an aluminum alloy described herein may have a yield strength of 260 MPa or greater, 270 MPa or greater, 280 MPa or greater, 290 MPa or greater, 300 MPa or greater, 310 MPa or greater, 320 MPa or greater, 325 MPa or greater, 330 MPa or greater, 335 MPa or greater, 340 MPa or greater, 345 MPa or greater, 350 MPa or greater, 355 MPa or greater, 360 MPa or greater, 365 MPa or greater, or 370 MPa or greater when in a T6 temper. In some cases, the yield strength when in the T6 temper is 250 MPa to 420 MPa (e.g., 260 MPa to 450 MPa, 280 MPa to 425 MPa, or 300 MPa to 400 MPa), or any value therebetween. The aluminum alloy products described herein may exhibit a yield strength as described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions (each corresponding to the rolling direction).
[0099] In some examples, the aluminum alloy products produced from the aluminum alloys described herein may have a yield strength of 200 MPa or more when in a T8x temper (2% pre-strain + 185°C for 20 minutes). For example, the aluminum alloy products produced from the aluminum alloys described herein may have a yield strength of 200 MPa or more, 210 MPa or more, 220 MPa or more, 230 MPa or more, 240 MPa or more, 250 MPa or more, 260 MPa or more, 270 MPa or more, 280 MPa or more, 290 MPa or more, or 300 MPa or more when in a T8x temper. In some cases, the yield strength when in the T8x temper is 200 MPa to 350 MPa (e.g., 210 MPa to 340 MPa, 220 MPa to 330 MPa, 230 MPa to 320 MPa, 240 MPa to 310 MPa, or 250 MPa to 300 MPa), or any value therebetween. The aluminum alloy products described herein may exhibit a yield strength as described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions (each corresponding to the rolling direction).
[0100] In some instances, the aluminum alloy product produced by the aluminum alloy described herein may have an ultimate tensile strength of about 300 MPa or greater when in T6 tempering. For example, the aluminum alloy product may have an ultimate tensile strength of 310 MPa or greater, 320 MPa or greater, 330 MPa or greater, 340 MPa or greater, 350 MPa or greater, 355 MPa or greater, 360 MPa or greater, 365 MPa or greater, 370 MPa or greater, 375 MPa or greater, 380 MPa or greater, 385 MPa or greater, or 390 MPa or greater when in T6 tempering. In some cases, the ultimate tensile strength is 300 MPa to 450 MPa (e.g., 300 MPa to 440 MPa, 325 MPa to 425 MPa, or 340 MPa to 400 MPa) or any value therebetween. The aluminum alloy products described herein may exhibit an ultimate tensile strength as described herein, when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions (each corresponding to a rolling direction).
[0101] In some instances, the aluminum alloy product produced by the aluminum alloy described herein may have an ultimate tensile strength of about 300 MPa or greater when in T8x tempering. For example, the aluminum alloy product may have an ultimate tensile strength of 310 MPa or greater, 320 MPa or greater, 330 MPa or greater, 340 MPa or greater, 350 MPa or greater, 355 MPa or greater, 360 MPa or greater, 365 MPa or greater, 370 MPa or greater, 375 MPa or greater, 380 MPa or greater, 390 MPa or greater, or 400 MPa or greater when in T8x tempering. In some cases, the ultimate tensile strength is 300 MPa to 450 MPa (e.g., 300 MPa to 440 MPa, 325 MPa to 425 MPa, or 340 MPa to 400 MPa) or any value therebetween when in T8x tempering. The aluminum alloy products described herein may exhibit an ultimate tensile strength as described herein, when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions (each corresponding to a rolling direction).
[0102] In some examples, an aluminum alloy product produced from the aluminum alloy described herein may have an incurvature angle of 100° to 140° (e.g., 105° to 140°, 105° to 135°, 105° to 130°, or 110° to 130°) when in a T6 temper, as measured in accordance with VDA 238-100 (2022). For example, an aluminum alloy product produced from the aluminum alloy described herein may have an incurvature angle of about 100°, 105°, 110°, 115°, 120°, 125°, 130°, 135°, 140°, 145°, 150°, 155°, or 160°, or any value therebetween, when in a T6 temper, as measured in accordance with VDA 238-100 (2022).
[0103] In some examples, when the aluminum alloy is in a T4 temper, an aluminum alloy product produced from the aluminum alloy described herein may have an intergranular corrosion depth of less than 450 microns when measured according to ISO 11846B (2022) for 24 hours (e.g., less than 425 microns, less than 400 microns, less than 375 microns, less than 350 microns, less than 325 microns, less than 300 microns, less than 275 microns, less than 250 microns, less than 225 microns, or less than 200 microns). In some examples, when the aluminum alloy is in a T4 temper, an aluminum alloy product produced from the aluminum alloy described herein may have an intergranular corrosion depth of 150 microns to 450 microns when measured according to ISO 11846B (2022) for 24 hours (e.g., 175 microns to 425 microns, 200 microns to 400 microns, 225 microns to 375 microns, 250 microns to 375 microns, 250 microns to 350 microns, or 260 microns to 340 microns).
[0104] In some examples, the aluminum alloy products produced from the aluminum alloys described herein may have an intergranular corrosion depth of less than 350 microns (e.g., less than 340 microns, less than 330 microns, less than 320 microns, less than 310 microns, less than 300 microns, less than 290 microns, less than 280 microns, less than 270 microns, less than 260 microns, or less than 250 microns) when measured for 24 hours according to ISO 11846B (2022) when the aluminum alloy is in T4 temper and subjected to 10% prestrain. In some examples, when the aluminum alloy is in T4 temper and subjected to 10% pre-strain, the aluminum alloy product produced from the aluminum alloy described herein may have an intergranular corrosion depth of 150 μm to 350 μm (e.g., 160 μm to 340 μm, 170 μm to 330 μm, 180 μm to 320 μm, 190 μm to 310 μm, 200 μm to 300 μm, or 200 μm to 290 μm) when measured for 24 hours according to ISO 11846B (2022).
[0105] Method for manufacturing aluminum alloy
[0106] The aluminum alloys described herein can be cast into cast products using a direct cooling (DC) process, or can be cast using a continuous casting (CC) process. The casting process is performed according to standards commonly used in the aluminum industry known to those skilled in the art. The CC process may include, but is not limited to, using a double belt casting machine, a double roll casting machine, or a block casting machine. In some instances, a casting process is performed by a CC process to form a slab, a strip, etc. In some instances, the casting process is a DC casting process to form a cast product.
[0107] Then the cast product, slab or strip can be subjected to further processing steps. Optionally, further processing steps can be used to prepare aluminum alloy products (e.g., sheets, Saudi plates or plates). Such processing steps include but are not limited to homogenization steps, hot rolling steps, cold rolling steps and optional painting steps. The processing steps for cast products are described below. However, using modifications known to those skilled in the art, the processing steps can also be used for casting slabs or strips.
[0108] In the homogenization step, the cast product may be heated to a homogenization temperature, such as a temperature in the range of 400°C to 600°C (e.g., 410°C to 590°C, 420°C to 580°C, 430°C to 560°C, 450°C to 550°C, 460°C to 550°C, 480°C to 550°C, or 500°C to 550°C). For example, the cast product may be heated to a temperature of 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, or 600°C. In some embodiments, the heating rate to the peak metal temperature may be 70°C / hour or less, 60°C / hour or less, or 50°C / hour or less. The cast product may then be allowed to soak (i.e., maintained at a specified temperature) for a period of time to form a homogenized product. In some examples, the total time for the homogenization step (including the heating phase and the soaking phase) may be up to 10 hours.
[0109] In some embodiments, the homogenization step described herein may be a two-stage homogenization. The first stage may include heating the cast product to a first homogenization temperature of about 350°C to about 450°C (e.g., 360°C to 440°C, 370°C to 430°C, 380°C to 420°C, or 400°C to 420°C). For example, the cast product may be heated to a temperature of 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, or 450°C. In some cases, the cast product is heated to a first homogenization temperature of 400°C to 420°C. In some cases, the heating rate for heating to the first homogenization temperature may be 70°C / hour or less, 60°C / hour or less, or 50°C / hour or less. The cast product is then allowed to soak (i.e., maintained at a specified temperature first homogenization temperature) for a period of time. In some cases, the cast product is soaked at the first homogenization temperature for up to 5 hours (e.g., 30 minutes to 5 hours, inclusive). For example, the cast product may be soaked at a first homogenization temperature of 350° C. to 450° C. for 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours. In some embodiments, the cast product may be soaked at a first homogenization temperature of 400° C. to 420° C. for 1 to 2 hours.
[0110] The second stage may include heating the cast product from the first homogenization temperature to a second homogenization temperature of 450°C to 550°C (e.g., 460°C to 540°C, 470°C to 530°C, 480°C to 520°C, or 480°C to 510°C). For example, the cast product may be heated to a temperature of 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, or 550°C. In some cases, the cast product is heated to a first homogenization temperature of 480°C to 510°C. The cast product is then allowed to soak for a period of time at the second homogenization temperature. In some cases, the cast product is soaked at the second homogenization temperature for up to 5 hours (e.g., 30 minutes to 5 hours, including end values). For example, the cast product may be soaked at a second homogenization temperature of 450°C to 550°C for 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours. In some embodiments, the cast product may be soaked at a second homogenization temperature of 480°C to 510°C for 0 to 2 hours.
[0111] After the homogenization step, a hot rolling step may be performed. The homogenized product may be hot rolled using a rolling mill to produce a hot rolled product. Before starting hot rolling, the homogenized product may be allowed to cool to a desired temperature such as 200°C to 425°C. For example, the homogenized product may be allowed to cool to a temperature of 200°C to 400°C, 250°C to 375°C, 300°C to 425°C, or 350°C to 400°C. The homogenized product may then be hot rolled at a hot rolling temperature (e.g., 200°C to 450°C) to produce a hot rolled product (e.g., hot rolled plate, hot rolled Saudi plate (hot rolled shate) or hot rolled sheet).
[0112] The hot rolled product can be cold rolled into a thinner product, such as a final gauge rolled product, using a cold rolling mill. The final gauge rolled product can have a gauge between 0.5 mm and 10 mm, for example, between 0.7 mm and 6.5 mm. Optionally, the final gauge rolled product can have the following gauges: 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, 8.5 mm, 9.0 mm, 9.5 mm, or 10.0 mm. Cold rolling may be performed to obtain a final gauge thickness representing a gauge reduction of up to 85% (e.g., a reduction of up to 10%, up to 20%, up to 30%, up to 40%, up to 50%, up to 60%, up to 70%, up to 80%, or up to 85%) compared to the gauge before cold rolling began. In some embodiments, the cold rolling step may include one or more cold rolling steps to achieve the desired gauge thickness reduction. Optionally, the process for producing the aluminum alloy may include an intermediate annealing step (e.g., between one or more cold rolling steps).
[0113] After hot rolling or cold rolling, the final specification rolled product can be subjected to solution heat treatment. The solution heat treatment step may include heating the final specification rolled product from room temperature to a temperature of 400°C to 600°C (e.g., 420°C to 580°C, from 440°C to 570°C, from 450°C to 560°C, from 460°C to 550°C, from 470°C to 540°C, from 480°C to 550°C, or from 500°C to 550°C). The final specification rolled product can be soaked at the temperature for a period of time. In some aspects, the final specification rolled product is allowed to soak for up to about 2 hours (e.g., 10 seconds to 120 minutes, including endpoints). For example, the rolled product of final specification can be soaked at a temperature of 400°C to 600°C for 20 seconds, 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, 65 seconds, 70 seconds, 75 seconds, 80 seconds, 85 seconds, 90 seconds, 95 seconds, 100 seconds, 105 seconds, 110 seconds, 115 seconds, 120 seconds, 125 seconds, 130 seconds, 135 seconds, 140 seconds, 145 seconds or 150 seconds, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, 60 minutes, 65 minutes, 70 minutes, 75 minutes, 80 minutes, 85 minutes, 90 minutes, 95 minutes, 100 minutes, 105 minutes, 110 minutes, 115 minutes or 120 minutes, or any value in between.
[0114] In some aspects, the heat treatment is performed immediately after the hot rolling or cold rolling step. In some aspects, the heat treatment is performed after the annealing step. The rolled product of the final specification can be naturally aged or artificially aged for a period of time to reach T temper. For example, the rolled product of the final specification can be aged to T4 temper, T6 temper or T8x temper (e.g., T81 temper). In some embodiments, the aluminum alloy is aged without pre-straining. In some embodiments, the aluminum alloy is artificially aged. In certain aspects, the rolled product in the final gauge in the T4 temper can be artificially aged (AA) for a period of time at 160° C. to 250° C. (e.g., 160° C., 165° C., 170° C., 175° C., 180° C., 185° C., 190° C., 195° C., 200° C., 205° C., 210° C., 215° C., 220° C., 225° C., 230° C., 235° C., 240° C., 245° C., or 250° C. Optionally, the rolled product in the final gauge can be artificially aged for a period of time of 15 minutes to 8 hours (e.g., 15 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours, or any value therebetween) to achieve a T6 temper.
[0115] Examples of suitable methods and alloy products
[0116] Example 1 is an aluminum alloy comprising 0.50 to 2.50 wt. % Si, 0.10 to 0.50 wt. % Fe, 0.01 to 1.20 wt. % Cu, 0.01 to 0.50 wt. % Mn, 0.30 to 1.50 wt. % Mg, 0.05 to 0.50 wt. % Cr, 0.01 to 0.50 wt. % Zn, up to 0.20 wt. % Zr, up to 0.15 wt. % impurities, and Al.
[0117] Example 2: An example as described in any preceding or subsequent example, wherein the aluminum alloy comprises 0.60 to 2.25 wt. % Si, 0.15 to 0.50 wt. % Fe, 0.01 to 1.00 wt. % Cu, 0.04 to 0.45 wt. % Mn, 0.35 to 1.30 wt. % Mg, 0.10 to 0.50 wt. % Cr, 0.01 to 0.40 wt. % Zn, up to 0.20 wt. % Zr, up to 0.15 wt. % impurities, and Al.
[0118] Example 3: An example as described in any preceding or subsequent example, wherein the aluminum alloy comprises 0.70 to 2.0 wt. % Si, 0.20 to 0.50 wt. % Fe, 0.05 to 1.00 wt. % Cu, 0.04 to 0.40 wt. % Mn, 0.40 to 1.20 wt. % Mg, 0.10 to 0.45 wt. % Cr, 0.01 to 0.30 wt. % Zn, up to 0.15 wt. % Zr, up to 0.15 wt. % impurities, and Al.
[0119] Example 4: An example as described in any preceding or subsequent example, wherein the aluminum alloy comprises 0.80 to 1.9 wt. % Si, 0.23 to 0.50 wt. % Fe, 0.20 to 1.00 wt. % Cu, 0.15 to 0.40 wt. % Mn, 0.45 to 1.00 wt. % Mg, 0.15 to 0.45 wt. % Cr, 0.01 to 0.20 wt. % Zn, 0.01 to 0.10 wt. % Zr, up to 0.15 wt. % impurities, and Al.
[0120] Example 5: An example as described in any preceding or subsequent example, wherein the aluminum alloy comprises 1.00 to 1.70 wt. % Si, 0.30 to 0.45 wt. % Fe, 0.30 to 0.80 wt. % Cu, 0.20 to 0.40 wt. % Mn, 0.50 to 0.90 wt. % Mg, 0.20 to 0.40 wt. % Cr, 0.01 to 0.15 wt. % Zn, 0.05 to 0.10 wt. % Zr, up to 0.15 wt. % impurities, and Al.
[0121] Example 6: An example as in any preceding or subsequent example, wherein the ratio of Cr:Cu is at least 0.25:1.
[0122] Example 7: An example as described in any preceding or subsequent example, wherein the aluminum alloy includes 0.20 to 0.50 wt % Cu, 0.05 to 0.30 wt % Cr, and a ratio of Cr:Cu of at least 0.3:1.
[0123] Example 8: An example as described in any preceding or subsequent example, wherein the aluminum alloy includes greater than 0.50 wt % Cu, 0.20 to 0.50 wt % Cr, and a ratio of Cr:Cu of at least 0.5:1.
[0124] Example 9: An example as in any preceding or subsequent example, wherein the aluminum alloy has a yield strength of at least 300 MPa when in T6 temper.
[0125] Example 10: The example of any preceding or subsequent example, wherein the aluminum alloy has an ultimate tensile strength of at least 350 MPa when in T6 temper.
[0126] Example 11: The example as described in any preceding or subsequent example, wherein the aluminum alloy includes a bend angle less than 140° when in T6 temper, as measured according to VDA 238-100 (2022).
[0127] Example 12: An example as in any preceding or subsequent example, wherein the aluminum alloy is pre-strained.
[0128] Example 13: An example as described in any preceding or subsequent example, wherein the aluminum alloy is pre-strained and has a maximum corrosion depth of less than 300 μm when subjected to the intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours.
[0129] Example 14: An example as in any preceding or subsequent example, wherein the aluminum alloy is in a T4 temper.
[0130] Example 15: An example as described in any preceding or subsequent example, wherein the maximum corrosion depth of the aluminum alloy is less than 400 μm when subjected to the intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours.
[0131] Example 16: A method for producing an aluminum alloy, comprising: casting an aluminum alloy to form a cast product, wherein the aluminum alloy contains 0.50 to 2.50 wt. % Si, 0.10 to 0.50 wt. % Fe, 0.01 to 1.20 wt. % Cu, 0.01 to 0.50 wt. % Mn, 0.30 to 1.50 wt. % Mg, 0.05 to 0.50 wt. % Cr, 0.01 to 0.50 wt. % Zn, up to 0.20 wt. % Zr, up to 0.15 wt. % impurities, and Al; homogenizing the cast product; hot rolling the cast product to produce a hot rolled product; cold rolling the rolled product to produce a rolled product of final specification; and solution heat treating the rolled product of final specification.
[0132] Example 17: The example as in any preceding or subsequent example, further comprising aging the rolled product to a final gauge to a T temper.
[0133] Example 18: An example as in any preceding or subsequent example, wherein the T temper is a T4 temper, a T6 temper, or a T8x temper.
[0134] Example 19: An example as in any preceding or subsequent example, further comprising pre-straining the rolled product to final gauge.
[0135] Example 20: An example as described in any preceding or subsequent example, further comprising naturally aging the rolled product of the final specification to T4 tempering, and artificially aging the rolled product of the final specification at a temperature of 150°C to 200°C for 10 min to 1 hour, wherein when subjected to the intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours, the maximum corrosion depth of the rolled product of the final specification is less than 300 μm.
[0136] The following examples will be used to further illustrate the present invention, but do not constitute any limitation of the present invention. On the contrary, it should be clearly understood that after reading the description herein, those skilled in the art themselves can think of adopting various embodiments, modifications and equivalent forms thereof without departing from the spirit of the present invention.
[0137] Example
[0138] Example 1
[0139] Sample aluminum alloys were tested to determine the properties of the aluminum alloys described herein. Comparative Examples 1-4 and Examples 1-5 were prepared according to the methods described herein. Comparative Examples 1-4 are conventional 6xxx series aluminum alloy compositions, which are currently used in automotive applications. Examples 1-5 were prepared from the aluminum alloys described herein, which contained 0.05 to 0.50 weight % Cr. Table 6 provides the aluminum alloy composition of each of Comparative Examples 1-4 and Examples 1-5.
[0140]
[0141] As shown in Table 6, Comparative Examples 1-4 are 6xxx series aluminums containing 0.54 to 0.91 wt % Cu. As discussed herein, 6xxx series aluminum alloys containing Cu are susceptible to increased IGC, especially when the Cu content is high. Embodiments 1-5 are 6xxx series aluminum alloys with different elemental components for evaluating the effects of Cr on alloy compositions with different amounts of Cu. The 6xxx series aluminum alloy compositions described herein are classified as low amounts of Cu (0.05 to 0.20 wt %), medium amounts of Cu (e.g., 0.20 to 0.50 wt %), and high amounts of Cu (greater than 0.50 wt %).
[0142] Figure 1 A graph of the maximum and average IGC depth (μm) for Comparative Examples 1-4 and Examples 1-5 is provided. Figure 1 The maximum and average IGC depths of Comparative Examples 1-4 and Examples 1-5, respectively, in T4 tempering and artificial aging at 180°C for 0.5 hours and in T4 tempering and 10% pre-strain plus artificial aging at 180°C for 1 hour are provided. Compared with Comparative Examples 1-4, Examples 1, 3 and 4 show lower maximum and average IGC depth values. In fact, Example 1, which contains 0.27 wt% Cr, shows better IGC resistance than Comparative Examples 1-4. In addition, although Example 1 has a higher amount of Cu, the IGC corrosion of Example 1 is lower than that of Comparative Examples 3 and 4. The improvement in IGC resistance of Example 1 can be attributed to the increase in the amount of Cr content in the alloy composition. As shown in Table 6, Example 1 contains 0.64 wt% Cu and 0.27 wt% Cr, Example 2 contains 0.56 wt% Cu and 0.02 wt% Cr, and Comparative Example 4 contains 0.54 wt% Cu and 0.01 wt% Cr. When the alloys were in T4 temper and artificially aged at 180°C for 0.5 hours, Comparative Examples 3 and 4 exhibited IGC maximum depths of 430 μm and 375 μm, respectively, while Example 1 with higher Cu and increased Cr content exhibited a maximum IGC depth of 256 μm.
[0143] In addition, Examples 4 and 5 are examples of low Cu 6xxx series aluminum alloy compositions with increased amounts of Cr. Specifically, Example 4 includes 0.04 wt % Cu and 0.06 wt % Cr, while Example 5 includes 0.03 wt % Cu and 0.10 wt % Cr. The IGC depth values for Example 4 and Example 5 are 229 μm and 183 μm, respectively. These findings demonstrate that adding Cr in alloys containing low Cu reduces the overall IGC depth in 6xxx series aluminum alloys. In fact, these findings demonstrate that adding Cr in 6xxx series aluminum alloys containing a wide range of Cu contents can improve IGC resistance.
[0144] Figure 2 Contour plots of the maximum IGC depths of Comparative Examples 1-4 and Examples 1-5 are provided, showing the relationship between the amount of Cr and Cu in the alloy composition and the IGC depth. Comparative Examples 1-4 and Examples 1-5 are all in T4 tempering and artificially aged for 0.5 hours at 180°C. Comparative Example 1 exhibits a maximum IGC depth of 328 μm. Comparative Example 3 and Example 2 each contain a high Cu content greater than 0.50 wt%, with Example 2 having the highest Cu content of 0.97 wt%. Although Example 2 has the highest Cu concentration, Example 2 exhibits a lower maximum IGC depth than Comparative Example 3. Example 2 has a higher Cr:Cu ratio (0.13:1) and exhibits better IGC resistance than Comparative Example 3 (0.4:1). The addition of Cr greatly improves the corrosion resistance of Example 2. When compared to Comparative Examples 1-4, Examples 1 and 3 also exhibit smaller maximum IGC depths (256 and 262 μm, respectively). Surprisingly, Example 3 contained more than twice the amount of Cu as Comparative Example 2 (0.26 wt% and 0.12 wt%, respectively), however, Example 3 exhibited a maximum IGC depth of 262 μm compared to 281 μm for Comparative Example 2, which may be attributed to the increased Cr content in Example 3 (0.31 wt% Cr compared to 0.01 wt% Cr in Comparative Example 2).
[0145] Examples 4 and 5 exhibit lower maximum IGC depths than Examples 1-3 and Comparative Examples 1-4, while the Cu level in the alloy composition is very low and the Cr level is slightly increased. Examples 4 and 5 each contain similar amounts of Cu, while Example 5 contains a higher Cr content. The higher Cr content in Example 5 results in a lower IGC depth. These results indicate that by increasing the Cr content (relative to the Cu content) of the aluminum alloy composition, the resulting properties are improved over conventional 6xxx series aluminum alloys.
[0146] Comparative Examples 1-4 and Examples 1-5 were evaluated to determine the effects of pre-strain and artificial aging on the IGC depth. The maximum IGC depth is Figure 3 Comparative Examples 1-4 and Examples 1-5 were in T4x temper, and then were 10% pre-strained and artificially aged at 180°C for 1 hour. Figure 2 and Figure 3 The maximum IGC depths of Comparative Examples 1-4 and Examples 1-5 shown in FIG. 7 are summarized in Table 7 below. Figure 3 As shown, pre-straining and extended aging improve the IGC resistance of high copper alloys (Examples 1-3), however, the IGC resistance of poor copper alloys (Examples 4 and 5) is not improved. Comparative Example 3, which is in T4 tempering and artificially aged for 0.5 hours at 180°C, shows a maximum IGC depth of 430μm. After 10% pre-strain and artificial aging for 1 hour at 180°C, Comparative Example 3 exhibits a maximum IGC depth of 285μm. That is, after pre-straining and extending the artificial aging time, the IGC erosion of Comparative Example 3 is reduced by 33.7%. After extended aging and pre-straining treatment, Examples 1 and 3 show improved IGC resistance compared to both Comparative Examples 1 and 2. Surprisingly, it was found that the combination of pre-straining and additional aging with Cr addition synergistically improved IGC resistance. It is considered that extended aging and pre-straining can reduce Cu segregation at grain boundaries, which can reduce the micro-galvanic effect between the Cu-rich film and the precipitation-free zone at the grain boundary, thereby reducing the susceptibility to IGC. These examples show that Cr addition significantly improves the IGC resistance of 6xxx series aluminum alloys with a wide range of Cu contents.
[0147]
[0148]
[0149] The microstructures of Example 1 and Comparative Example 3 were studied to determine the effect of Cr addition on the grain boundary microstructure, which is related to IGC resistance. The grain boundary microstructures of Example 1 and Comparative Example 3 were characterized using a scanning transmission electron microscope (STEM). FIG. 4A to FIG. 4D Example 1 ( Figure 4A and Figure 4C ) and Comparative Example 3 ( Figure 4B and Figure 4D ) of the grain boundary. Figure 4A and Figure 4B As shown, Example 1, which contains 0.64 wt% Cu and 0.27 wt% Cr, exhibits a higher dispersoid number density due to the addition of Cr than Comparative Example 3, which contains 0.56 wt% Cu and 0.02 wt% Cr. The grain boundary microstructures of Example 1 and Comparative Example 3 are very different. The microstructure of Example 1 includes some elongated precipitates at the grain boundaries, where Figure 4CThere are some fine particles at one of the grain boundaries indicated by the arrows. Figure 4D As shown by the arrows in , many fine and elongated precipitates are observed at the grain boundaries of Comparative Example 3. When compared with Comparative Example 3, the difference at the grain boundaries is likely due to the increased Cr content in Example 1, given that the alloy components are relatively the same except for Cr.
[0150] In order to further study the grain boundary microstructure, the samples of Example 1 ( Figure 5A ) and Comparative Example 3 ( Figure 5B and Figure 5C ). Figure 5A As shown, Example 1 contains some dispersoids containing Al, Fe, Si, Cr and Mn in the microstructure (solid arrows), and contains precipitated phase particles in the microstructure, specifically, a small amount of Q phase precipitates containing Al, Mg, Si and Cu (dashed arrows, 5A at the grain boundary). For Comparative Example 3, the sample was tilted during STEM imaging so that the electron beam was parallel to the grain boundary plane. Figure 5B and Figure 5C It is shown that the grain boundaries of Comparative Example 3 include a large number of Q phase precipitates containing Cu, such as Figure 5B As shown by the dashed arrows in . The higher Cr content in Example 1 provides grain boundaries with less Q phase than that in Comparative Example 3, thereby reducing IGC.
[0151] Fig. 6A shows a bright field STEM image of Example 1, and FIG. 6B to FIG. 6H Energy dispersive X-ray spectroscopy (EDS) graphs showing the contents of Al, Mg, Si, Cu, Fe, Cr and Mn in the alloy composition are shown respectively. The microstructure of Example 1 comprises Q phase precipitates containing Si, Al, Mg and Cu, such as FIG. 6B to FIG. 6E As indicated by the arrow in . Fig. 7A The dark field STEM image of Comparative Example 3 is shown. FIG. 7B to FIG. 7H An EDS graph showing the Al, Mg, Si, Cu, Fe, Cr and Mn contents in the alloy composition is shown. 7B to 7H The EDS image of Comparative Example 3 in Figure 1 shows that Q phase precipitates are formed at the grain boundaries, indicated by solid arrows, while Si and Mg are depleted at the grain boundaries between Q phases. However, Cu is present at the grain boundaries, as indicated by dashed arrows. The Cu-rich film at the grain boundaries and the fine and closely spaced Q phase precipitates can act as cathodes to drive IGC, demonstrating the increased susceptibility of Comparative Example 3 to IGC. Cr at the grain boundaries in Example 1 can control the grain size and change the grain boundary microstructure by forming dispersoids, thereby improving IGC resistance.
[0152] In order to better understand the microstructures of Example 1 and Comparative Example 3, electron backscatter diffraction (EBSD) analysis was performed. Figure 8 shows that Example 1 and Comparative Example 3 have different microstructures based on the EBSD images. Specifically, due to the formation of dispersoids in Example 1, Example 1 exhibits smaller grains than Comparative Example 3. The reduced grain size can affect the diffusion of solutes to grain boundaries, reduce Cu segregation and the formation of Q phase, and thus reduce the driving force for the occurrence of IGC.
[0153] The yield strength, ultimate tensile strength and elongation of Comparative Examples 1-4 and Example Alloys 1-5 were evaluated to understand the influence of Cr on the mechanical properties of 6xxx series aluminum alloys. As shown in Table 8, due to the different amounts of Mg and Cu in each aluminum alloy, Comparative Examples 1-4 exhibit different yield strengths. In addition, compared with T8x tempering, Comparative Examples 1-4 exhibit higher yield strengths when in T6 tempering. For copper-poor 6xxx series aluminum alloys, such as Example Alloys 4 and 5, yield strength is not affected by Cr addition.
[0154] Table 8 also includes the tensile strength of the alloy composition under tempering and pre-strained state or under tempering alone. These results show that increasing copper does increase the tensile strength of the alloy. In addition, adding Cr to resist the IGC of the alloy does not reduce the tensile strength of the alloy composition. At the same time, the formability of the alloy composition is evaluated by the bending angle. Comparative Examples 1-4 and Embodiments 1-5 have a considerable bending angle. These results show that the aluminum alloy described herein shows similar strength and bending properties. In addition, the results show that the alloy composition can include a higher amount of Cr content to reduce IGC while still maintaining physical properties comparable to current 6xxx series aluminum alloys.
[0155]
[0156] 6xxx series aluminum alloys include Cu as a strengthening element to achieve high strength. However, as previously mentioned, 6xxx series aluminum alloys containing a large amount of Cu are more prone to IGC. Example alloys described herein show that Cr can be added to 6xxx series aluminum alloys containing Cu to improve corrosion resistance. 6xxx series aluminum alloys comprising the Cr of the amount described herein can improve IGC resistance while maintaining the formability, strength and elongation of the alloy.
[0157] All patents, publications and abstracts cited above are incorporated herein by reference in their entirety. In order to achieve the various objects of the present invention, various embodiments of the present invention have been described. It should be appreciated that these embodiments are only intended to illustrate the principles of the present invention. Various modifications and alterations thereof will be apparent to those skilled in the art without departing from the spirit and scope of the present invention as defined in the following claims.
Claims
1. An aluminum alloy comprising 0.50 to 2.50 wt % Si, 0.10 to 0.50 wt % Fe, 0.01 to 1.20 wt % Cu, 0.01 to 0.50 wt % Mn, 0.30 to 1.50 wt % Mg, 0.05 to 0.50 wt % Cr, 0.01 to 0.50 wt % Zn, up to 0.20 wt % Zr, up to 0.15 wt % impurities, and Al.
2. The aluminum alloy of claim 1, wherein the aluminum alloy comprises 0.60 to 2.25 wt. % Si, 0.15 to 0.50 wt. % Fe, 0.01 to 1.00 wt. % Cu, 0.04 to 0.45 wt. % Mn, 0.35 to 1.30 wt. % Mg, 0.10 to 0.50 wt. % Cr, 0.01 to 0.40 wt. % Zn, up to 0.20 wt. % Zr, up to 0.15 wt. % impurities, and Al.
3. The aluminum alloy of claim 1, wherein the aluminum alloy comprises 0.70 to 2.0 wt. % Si, 0.20 to 0.50 wt. % Fe, 0.05 to 1.00 wt. % Cu, 0.04 to 0.40 wt. % Mn, 0.40 to 1.20 wt. % Mg, 0.10 to 0.45 wt. % Cr, 0.01 to 0.30 wt. % Zn, up to 0.15 wt. % Zr, up to 0.15 wt. % impurities, and Al.
4. The aluminum alloy of claim 1, wherein the aluminum alloy comprises 0.80 to 1.9 wt. % Si, 0.23 to 0.50 wt. % Fe, 0.20 to 1.00 wt. % Cu, 0.15 to 0.40 wt. % Mn, 0.45 to 1.00 wt. % Mg, 0.15 to 0.45 wt. % Cr, 0.01 to 0.20 wt. % Zn, 0.01 to 0.10 wt. % Zr, up to 0.15 wt. % impurities, and Al.
5. The aluminum alloy of claim 1, wherein the aluminum alloy comprises 1.00 to 1.70 wt. % Si, 0.30 to 0.45 wt. % Fe, 0.30 to 0.80 wt. % Cu, 0.20 to 0.40 wt. % Mn, 0.50 to 0.90 wt. % Mg, 0.20 to 0.40 wt. % Cr, 0.01 to 0.15 wt. % Zn, 0.05 to 0.10 wt. % Zr, up to 0.15 wt. % impurities, and Al.
6. The aluminum alloy of claim 1, wherein the ratio of Cr:Cu is at least 0.25:
1.
7. The aluminum alloy of claim 1, wherein the aluminum alloy comprises 0.20 to 0.50 wt. % Cu, 0.05 to 0.30 wt. % Cr, and a ratio of Cr:Cu of at least 0.3:
1.
8. The aluminum alloy of claim 1, wherein the aluminum alloy comprises greater than 0.50 wt. % Cu, 0.20 to 0.50 wt. % Cr, and a ratio of Cr:Cu of at least 0.5:
1.
9. The aluminum alloy of claim 1, wherein the aluminum alloy has a yield strength of at least 300 MPa when in T6 temper.
10. The aluminum alloy of claim 1, wherein the aluminum alloy has an ultimate tensile strength of at least 350 MPa when in T6 temper.
11. The aluminum alloy of claim 1, wherein the aluminum alloy comprises an inward bend angle of less than 140° when in T6 temper, as measured according to VDA 238-100 (2022).
12. The aluminum alloy of claim 1, wherein the aluminum alloy is pre-strained.
13. The aluminum alloy of claim 12, wherein the aluminum alloy is pre-strained, and when subjected to an intergranular corrosion (IGC) test specified in ISO11846B (2022) for 24 hours, the maximum corrosion depth of the aluminum alloy is less than 300 μm.
14. The aluminum alloy of claim 1, wherein the aluminum alloy is in a T4 temper.
15. The aluminum alloy of claim 14, wherein when subjected to an intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours, the maximum corrosion depth of the aluminum alloy is less than 400 μm.
16. A method for producing an aluminum alloy, comprising: Casting an aluminum alloy to form a cast product, wherein the aluminum alloy comprises 0.50 to 2.50 wt % Si, 0.10 to 0.50 wt % Fe, 0.01 to 1.20 wt % Cu, 0.01 to 0.50 wt % Mn, 0.30 to 1.50 wt % Mg, 0.05 to 0.50 wt % Cr, 0.01 to 0.50 wt % Zn, up to 0.20 wt % Zr, up to 0.15 wt % impurities, and Al; homogenizing the cast product; hot rolling the cast product to produce a hot rolled product; cold rolling the rolled product to produce a rolled product of final specifications; as well as The rolled product of the final specification is solution heat treated.
17. The method of claim 16, further comprising aging the final gauge rolled product to a T temper.
18. The method of claim 17, wherein the T temper is a T4 temper, a T6 temper, or a T8x temper.
19. The method of claim 16, further comprising pre-straining the final gauge rolled product.
20. The method of claim 16, further comprising subjecting the rolled product of the final specification to natural aging to T4 tempering and artificial aging the rolled product of the final specification at a temperature of 150°C to 200°C for 10 min to 1 hour, wherein when subjected to the intergranular corrosion (IGC) test specified in ISO 11846B (2022) for 24 hours, the maximum corrosion depth of the rolled product of the final specification is less than 300 μm.